Análisis del gasto de bolsillo ante la enfermedad de personas de 60 y más años según su condición de pobreza en Paraguay - E Giménez; R Caballero; N Peralta; J.M Araujo (Instituto Nacional de Salud (INS), 2019)
Introduction:Reducing poverty and achieving universal health coverage for people of all ages are part of the Sustainable Development Goal. Objective:determine the Out-of-pocket Health Expenditure (GBS) for people 60 and older (≥ 60 years) who are sick and its economic impact on households according to their poverty status in Paraguay. Material and Method: the 2014 Permanent Household Survey was analyzed, considering the official definition of poverty and the reference of illness or accident in a quarter. The average of GBS per household, the impact on quarterly monetary risk (IM) and on state subsidies for food pensions for the elderly (IPa). Results:Of 1,621,525 homes in the country 435,448 had at least 1 person 60 years, of which 188,715 had at least 1 of them ill or injured and 144,554 reported GBS. Among the non-poor households: 11.6% (IC 10.5 to 12.9) had at least 1 ill person ≥ 60 years, of which 75.8% (IC 71.2 to 79.8) had GBS, being on average 547,931 Gs. (DE 58,251). The medications were 53.3% (IC 45.2 to 61.5) from total. There was an IM of 5,7% (IC 4.6 to 6.9). Among the poor households: 11.6% (IC 9.6 to 14.0) had at least 1 ill person ≥ 60 years, of which 79.5% (IC 70.7 to 86,2) had GBS, being on average 341,542 Gs. (DE 40,101). The medications were 71.3 % (IC 61.9 to 80.7) from total. There was an IM of 11.5% (IC 7.0 to 16.0). There was an IPa of 16.9% (IC 4.4 to 29.4). The GBS was the equivalent to 19 days of feeding on average (DE 3.71). Conclusion: Paraguay requires more financial protection for older adults through synergies of poverty reduction and health policies.